2021
DOI: 10.1038/s41598-021-82713-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple objects interacting with a solidification front

Abstract: The interaction of objects suspended in a liquid melt with an advancing solidification front is of special interest in nature and engineering sciences. The front can either engulf the object into the growing crystal or repel it. Therefore, the object-front confrontation can have a strong influence on the microstructure and mechanical or functional properties of the solidified material. The past theoretical models and experimental studies have mostly investigated the interaction of isolated, spherical, and hard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…1. Deville has recently reported 95 experiments where a growing planar freezing front encounters monodisperse oil droplets of different sizes. They show that isolated droplets…”
Section: Interaction Of the Solute With The Freezing Frontmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Deville has recently reported 95 experiments where a growing planar freezing front encounters monodisperse oil droplets of different sizes. They show that isolated droplets…”
Section: Interaction Of the Solute With The Freezing Frontmentioning
confidence: 99%
“…1. Deville has recently reported 95 experiments where a growing planar freezing front encounters monodisperse oil droplets of different sizes. They show that isolated droplets are rejected at the freezing front when they are smaller than a critical size while larger droplets are engulfed.…”
Section: Interaction Of the Solute With The Freezing Frontmentioning
confidence: 99%
“…17 Furthermore, recent investigations involving “soft” particles, such as droplets or bubbles, have shown that the overall complexity is further amplified due to the mechanical deformation experienced by the particles during the interaction with the moving solidification front. 18–20…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, recent investigations involving ''soft'' particles, such as droplets or bubbles, have shown that the overall complexity is further amplified due to the mechanical deformation experienced by the particles during the interaction with the moving solidification front. [18][19][20] The current understanding of this subject primarily stems from studying the interaction between uniform particles and a moving solidification interface. However, in modern technological applications, such as cryobiology and material science, complex and multicomponent particles are frequently encountered.…”
Section: Introductionmentioning
confidence: 99%